Health economic design for cost, cost-effectiveness and simulation analyses in the HEALing Communities Study. (1st December 2020) - Aldridge, Arnie P.; Barbosa, Carolina; Barocas, Joshua A.; Bush, Joshua L.; Chhatwal, Jagpreet; Harlow, Kristin J.; Hyder, Ayaz; Linas, Benjamin P.; McCollister, Kathryn E.; Morgan, Jake R.; Murphy, Sean M.; Savitzky, Caroline; et al.
Highlights: The HEALing Communities Study is designed to implement and evaluate the Communities That HEAL intervention to reduce opioid overdose deaths. The HCS includes a health economics study. Costs of CTH will be estimated for multiple perspectives. The health economics study includes cost-effectiveness analyses and simulation modeling. Abstract: Background: The HEALing Communities Study (HCS) is designed to implement and evaluate the Communities That HEAL (CTH) intervention, a conceptually driven framework to assist communities in selecting and adopting evidence-based practices to reduce opioid overdose deaths. The goal of the HCS is to produce generalizable information for policy makers and community stakeholders seeking to implement CTH or a similar community intervention. To support this objective, one aim of the HCS is a health economics study (HES), the results of which will inform decisions around fiscal feasibility and sustainability relevant to other community settings. Methods: The HES is integrated into the HCS design: an unblinded, multisite, parallel arm, cluster randomized, wait list–controlled trial of the CTH intervention implemented in 67 communities in four U.S. states: Kentucky, Massachusetts, New York, and Ohio. The objectives of the HES are to estimate the economic costs to communities of implementing and sustaining CTH; estimate broader societal costs associated with CTH; estimate the cost-effectiveness of CTH for overdose deaths avoided; and use simulation modeling to evaluate the short- and long-term health and economic impact of CTH, including future overdose deaths avoided and quality-adjusted life years saved, and to develop a simulation policy tool for communities that seek to implement CTH or a similar community intervention. Discussion: The HCS offers an unprecedented opportunity to conduct health economics research on solutions to the opioid crisis and to increase understanding of the impact and value of complex, community-level interventions.